Old Drug, New Pain. Roles and Challenges of Methadone Therapy in Pediatric Palliative Care: A Systematic Review - Benedetti, Francesca; Zoletto, Silvia; Salerno, Annalisa; Avagnina, Irene; Benini, Franca (Frontiers in Pediatrics, 2022)
Pediatric palliative care (PPC) the prevention and relief from suffering of families and children with life-limiting (LLDs) or life-threatening diseases (LTDs). These patients often experience pain, with morphine being the most widely used drug. Few studies investigated the role of methadone in PPC, although it is considered among the most effective drugs. Our aim was to evaluate efficacy, safety, and dosage of methadone in PPC. Between August and October 2021 Pubmed, Scopus and the Cochrane Library were searched for studies on the use of methadone in children with LLDs and LTDs. Articles were included if: published in the last 10 years, English language, patients aged 0-23 years and enrolled in a PPC center or receiving declared support from a PPC service; reporting of specific data on methadone in trials, observational studies, or case series on >10 patients. Reporting of the article was guided by the PRISMA guidelines; critical appraisal was performed using the JBI-tool. Four studies were included and another one was added after checking the references of the retrieved papers. All were retrospective, the literature is concordant in documenting the lack of evidence. A total of 116 children received methadone in PPC. From our review emerges the poor quality of data collection: in only one study pain was assessed with standardized scales. All studies documented the effectiveness of methadone in treating complex pain. No serious adverse events were reported. Our results suggest that methadone could represent a suitable strategy for treating pain in PPC. However, further research is warranted.